Factors affecting mortality in COVID-19 patients treated with intravenous immunoglobulin (Annals of Medical Research, 2023)
Aim: Intravenous immunoglobulin (IVIG), used as an option in the treatment of severe Coronavirus disease 2019 (COVID-19), has been shown to have effects on the suppression of the hyperinflammatory state through immunomodulatory actions. The aim of our study was to evaluate the factors associated with mortality in patients treated with IVIG for COVID-19.Materials and Methods: Patients diagnosed with COVID-19 and receiving IVIG therapy in addition to standard care therapy were included in the study.Results: A total of 46 patients who received IVIG treatment were included in the study. The mortality rate was higher in patients aged over 52 years (p:
Keywords: COVID-19; Intravenous immunoglobulin; Charlson Comorbidity Index; Immunoglobulin A; Mortality